Association of Plasma Interferon-a(IFN-a) with C-Reactive Protein (CRP) Level and Disease Activity in Systemic Lupus Erythematosus (SLE) Patients - Awalia; Harianto Notopuro; Joewono Soeroso (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: CRP is normal or only slightly increased in active SLE. It is presumed that IFN-α mayinhibit the transcription process during CRP synthesis. There is also increasing in IFN-αgene expressionin active SLE. This study examined the correlation of plasma IFN-α with CRP and SLE activity.Methods:Forty SLE patients were included. SLAM and SLEDAI were used to measure SLE diseaseactivity. Laboratory tests were examined at dr.Soetomo Hospital Surabaya. CRP was measured usingimmunoturbidimetry. C3 and C4 were measured by radial immunodiffusion technique. IFN-αwasmeasured using ELISA.Results and conclusion:Twenty-six patients from the outpatient clinic and 14 from wards wereincluded from August 2019 to February 2020. The median age was 31.5 years old. The median SLAMscore was 8.5. Mean CRP was 5.19±2.69 mg/L. Median plasma IFN-α was 46.02 (16.43-177.96).Spearman correlation test revealed a moderate negative correlation between plasma IFN-α and CRPlevel (p=0.003; r=-0.455). A moderate positive correlation was showed between plasma IFN-α leveland SLAM score (p=0.001; r=0.568). No correlation found between CRP and SLAM. There was astrong correlation between complement levels with SLEDAI. Linear regression revealed a significantassociation of IFN-α and C3 (not C4) level with SLEDAI.